Decentralisation in Cameroon and the Anglophones’ Struggle for Autonomy - Epongo, Emmanuel Makia (University of the Witwatersrand, Johannesburg, 2023)
In Cameroon, decentralisation was introduced in 1996 to promote development, democracy and good governance at the local level. However, decentralisation exacerbated conflicts between the Anglophone minority and the Francophone-majority government, resulting in a civil war in 2017. Therefore, this research explores how the implementation of decentralisation in the two Anglophone regions exacerbated conflicts between the Anglophone minority and the Francophone-majority government. Despite the growing literature on decentralisation and conflicts, very little research has been conducted on conflicts arising from former independent colonial territories that reunited under a federal system and later evolved to a decentralised unitary system, a shortcoming addressed by this research. This study used qualitative methodology and a case study design. The research was conducted at the Kumba and Bamenda city councils in the Southwest and Northwest regions, respectively. Participants were selected through purposive and snowball sampling techniques for semi-structured interviews. Data from interviews, observation and archival documents were merged and analysed through thematic analysis. The findings suggest that decentralisation in the Anglophone regions is more of deconcentration than devolution. Understanding how decentralisation increased intrastate conflict between the Anglophone minority and the Francophone-majority government could have a broader significance for researchers, governments and policymakers seeking to mitigate conflicts, particularly in Africa, with diverse societies prone to intrastate conflicts
A thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in fulfillment of the requirements for the degree of Doctor of Philosophy, Johannesburg 2023
Keywords: UCTD; Decentralisation; Intrastate conflicts; Mitigate conflicts; Eroded autonomy; Divided societies; SDG-17: Partnerships for the goals